VEGF as a potential target in lung cancer. (3rd October 2017) - Frezzetti, Daniela; Gallo, Marianna; Maiello, Monica R.; D'Alessio, Amelia; Esposito, Claudia; Chicchinelli, Nicoletta; Normanno, Nicola; De Luca, Antonella
ABSTRACT: Introduction The vascular endothelial growth factor A (VEGF) is the main mediator of angiogenesis. In addition, VEGF contributes to cancer growth and metastasis directly targeting tumor cells. VEGF overexpression and/or high VEGF serum levels have been reported in lung cancer. Areas covered We searched Pubmed for relevant preclinical studies with the terms 'lung cancer' 'VEGF' and ' in vivo '. We also searched the Clinicaltrials.gov database, the FDA and the EMA websites for the most recent updates on clinical development of anti-VEGF agents. Expert opinion VEGF plays an important role in sustaining the development and progression of lung cancer and it might represent an attractive target for therapeutic strategies. Nevertheless, clinical trials failed to attend the promising expectations deriving from preclinical studies with anti-VEGF agents. To improve the efficacy of anti-VEGF therapies in lung cancer, potential strategies might be the employment of combinatory therapies with immune checkpoint inhibitors or agents that inhibit signaling pathways and proangiogenic factors activated in response to VEGF blockade, and the identification of novel targets in the VEGF cascade. Finally, the identification of predictive markers might help to select patients who are more likely to respond to anti-angiogenic drugs.